Pengaruh Kinerja Hutang Terhadap Nilai Perusahaan pada Perusahaan Pertambangan Batubara yang Terdaftar di BEI Periode 2010-2013 - Khairudin KHAIRUDIN; Rico Tanto (Universitas Bandar Lampung (UBL), 2015)
The primary goal of the company is to maximize firm value. Firm value is investor perceptionof the company's success rate, it is often associated with stock prices. This research aim to examine the effect of leverage towards the value of the company in the coal mining companies which listed on the Indonesia Stock Exchange with periods 2010-2011. The hypothesis was leverage has negative effect on firm value. This research uses secondary data, of the coal mining companies which listed on BEI with periods 2010-2013. Research sample of 15 companies, where the method used is purposive sampling is a sampling method that takes an object with the specified criteria. Leverage are measured using Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR). Meanwhile, firm value is measured using Price Earning Ratio (PER). Analysis of the data used to analyze the factor that affect firm value is simple linier regression analysis and hypothesis test used the t-statistic for testing the partial regression coeffiecient at level of significant 5%. The results of this research finds leverage (DER) has negative significant effect on firm value (PER) with predictive ability is 6,8% and it shown by R square, and leverage (DAR) has negative significant effect on firm value (PER) with predictive ability is 7,2% and it shown by R square.